The Influence Of Mnemonic Learning Models On Plant Tissue Material On Learning Outcomes Of Class XI Students Of SMA Negeri 4 Manado - Mirayanti Banapon; Debby J. J. Rayer; Danny Ch. Posumah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The low student learning results may be observed in the value decided by the teacher, which is less than the KKM's average value of 75. The purpose of this study is to determine the impact of the mnemonic learning model on student biology learning outcomes in class XI MIPA SMA Negeri 4 Manado during the academic year 2021/2022. This study used a quasi-experimental design. This study's sample included two classes: class XI MIPA 1 as an experimental class with 20 students and class X1 MIPA 2 as a control class with 20 students. The results showed that the average pretest and post-test learning outcomes obtained by students in class XI MIPA 1 (experiment) with the application of the pretest mnemonic learning model were 34.75 and 76.75, respectively, while the pretest and post-test learning outcomes obtained by students in class XI IPA 2 (control) with only conventional learning were 31.25 and 71.25, respectively. The value of tcount> ttable was derived by hypothesis testing the pretest and post-test data in the experimental and control classes at a significant threshold of 0.05. The table value is 2.024, whereas the count value is 2.681. H0 is rejected based on the hypothesis testing criterion, but H1 is approved. This suggests that H0 has no effect, however H1 has an affect on student learning outcomes in Biology class XI at SMA Negeri 4 Manado.